Non-pharmacological treatment in high blood pressure - Sztandera, Paulina (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work. High blood pressure causes an early death of people all over the world. It develops circulatory system diseases such as: heart attack, stroke, heart failure, peripheral artery disease, and also kidney failures. The following factors could have an influence on high blood pressure: age, sex, physical activity, stress, force contracting the heart, circulated blood, and resistance of blood vessels. The purpose of the study was to analyze the literature of non-pharmacological treatment of high blood pressure.Brief description of the state of the art. Non-pharmacological treatment consists mainly in changing the lifestyle, i.e. quitting smoking, reducing the weight, decreasing alcohol consumption, reducing salt consumption, increasing physical activity level, consuming fruit and vegetables, decreasing consumption of saturated fat and the total fat intake.Summary (conclusions). Non-pharmacological treatment should be abided by each patient with high blood pressure. That kind of non-pharmacological treatment brings a lot of advantages, such as decreased blood pressure, better clinical observations and decreased therapeutic dose of hypertensive drugs.